First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Extreme Heatwave Causes Immediate, Widespread Mortality of Forest Canopy Foliage, Highlighting Modes of Forest Sensitivity to Extreme Heat - Adam Sibley; Christopher Still; Matthew Gregory; Constance Harrington; David Shaw; Nina Ferrari; Alex Dye; Mark Schulze; Glenn Howe; David E. Rupp; Christopher Daly; Daniel DePinte; et al. (Global Change Biology, 2025)
In late June 2021, multiple days of record‐breaking heat caused an unprecedented amount of foliage death in the forests of the Pacific Northwest, USA. Portions of tree canopies with healthy green foliage prior to the heat changed to red or orange shortly after the event. The change in foliage color could be readily seen in satellite imagery and was corroborated as foliar death (heat scorch) by aerial surveys and extensive observations on the ground. To better understand the patterns and processes driving foliar death, we used satellite imagery to identify 293,546 ha of forest, or ~4.7% of forest area, that were damaged in western Oregon and Washington by this extreme heat event. Analysis of underlying drivers of the observed heat damage indicated greater sensitivity was related to abiotic factors such as sun exposure, aspect, and microclimate, as well as biotic factors like tree species and stand age, budburst phenology, and foliar pathogens impacting tree health. Iconic, culturally and economically significant species like western redcedar, western hemlock, and Sitka spruce were disproportionately sensitive to heat damage, including in old‐growth stands where they are canopy dominants. These findings highlight the multifaceted challenges posed to forests by extreme heat waves, and the need to better understand their impact on forest ecosystems in a rapidly warming climate.

Microplastic consumption elevates fish oxidative stress but does not affect predator-driven mortality - Amelia M. Mannering; David J. Burritt; Valeriya Komyakova; Maud C.O. Ferrari; George Vamvounis; Alexandra M. Gulizia; Adam Staples; Mark I. McCormick; Bridie J.M. Allan (Science of The Total Environment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Wastewater based measures of COVID-19 and associations with children's absenteeism at grade schools - Helena M. Solo-Gabriele; Gabriela Guevara; Naresh Kumar; Ayaaz Amirali; Kristina M. Babler; Cynthia C. Beaver; Samuel Comerford; Maria Ferraris; Natasha Schaefer Solle; Mark E. Sharkey; Lisa Gwynn (Science of The Total Environment, 2025)

Variations in benthic foraminifera biofacies since Mid-Pleistocene (MIS 7) in the Campos Basin slope, Eastern Brazil: Assessing present-day and past controlling factors - Sarah Pereira Gasparini; Claudia Gutterres Vilela; Mark Maslin; Kimmolly Ferrari Ferreira (Marine Micropaleontology, 2023)

Disturbance cues facilitate associative learning of predators in a coral reef fish - Michael S. Pollock; Zoe Hoyle; Mark I. Mccormick; Douglas P. Chivers; Maud C. O. Ferrari (Behavioral Ecology and Sociobiology, 2021)

Exposure to degraded coral habitat depresses oxygen uptake rate during exercise of a juvenile reef fish - Adam T. Downie; Caroline M. Phelps; Rhondda Jones; Jodie L. Rummer; Douglas P. Chivers; Maud C. O. Ferrari; Mark I. McCormick (Coral Reefs, 2021)

Refugia under threat: Mass bleaching of coral assemblages in high‐latitude eastern Australia - Sun W. Kim; Eugenia M. Sampayo; Brigitte Sommer; Carrie A. Sims; Maria del C. Gómez‐Cabrera; Steve J. Dalton; Maria Beger; Hamish A. Malcolm; Renata Ferrari; Nicola Fraser; Will F. Figueira; Stephen D. A. Smith; et al. (Global Change Biology, 2019)
Environmental anomalies that trigger adverse physiological responses and mortality are occurring with increasing frequency due to climate change. At species' range peripheries, environmental anomalies are particularly concerning because species often exist at their environmental tolerance limits and may not be able to migrate to escape unfavourable conditions. Here, we investigated the bleaching response and mortality of 14 coral genera across high‐latitude eastern Australia during a global heat stress event in 2016. We evaluated whether the severity of assemblage‐scale and genus‐level bleaching responses was associated with cumulative heat stress and/or local environmental history, including long‐term mean temperatures during the hottest month of each year (SST LTMAX ), and annual fluctuations in water temperature (SST VAR ) and solar irradiance (PARZ VAR ). The most severely‐bleached genera included species that were either endemic to the region ( Pocillopora aliciae ) or rare in the tropics (e.g. Porites heronensis ). Pocillopora spp., in particular, showed high rates of immediate mortality. Bleaching severity of Pocillopora was high where SST LTMAX was low or PARZ VAR was high, whereas bleaching severity of Porites was directly associated with cumulative heat stress. While many tropical Acropora species are extremely vulnerable to bleaching, the Acropora species common at high latitudes, such as A. glauca and A. solitaryensis , showed little incidence of bleaching and immediate mortality. Two other regionally‐abundant genera, Goniastrea and Turbinaria , were also largely unaffected by the thermal anomaly. The severity of assemblage‐scale bleaching responses was poorly explained by the environmental parameters we examined. Instead, the severity of assemblage‐scale bleaching was associated with local differences in species abundance and taxon‐specific bleaching responses. The marked taxonomic disparity in bleaching severity, coupled with high mortality of high‐latitude endemics, point to climate‐driven simplification of assemblage structures and progressive homogenisation of reef functions at these high‐latitude locations.

Terrestrial Behavior in Titi Monkeys (Callicebus, Cheracebus, and Plecturocebus): Potential Correlates, Patterns, and Differences between Genera - João Pedro Souza-Alves; Italo Mourthe; Renato R. Hilário; Júlio César Bicca-Marques; Jennifer Rehg; Carla C. Gestich; Adriana C. Acero-Murcia; Patrice Adret; Rolando Aquino; Mélissa Berthet; Mark Bowler; Armando M. Calouro; et al. (International Journal of Primatology, 2019)

The Role of Stakeholders in Creating Societal Value From Coastal and Ocean Observations - Bev Mackenzie; Louis Celliers; Luiz Paulo de Freitas Assad; Johanna J. Heymans; Nicholas Rome; Julie Thomas; Clarissa Anderson; James Behrens; Mark Calverley; Kruti Desai; Paul M. DiGiacomo; Samy Djavidnia; et al. (Frontiers in Marine Science, 2019)

Habitat degradation disrupts neophobia in juvenile coral reef fish - Mark I. McCormick; Douglas P. Chivers; Bridie J. M. Allan; Maud C. O. Ferrari (Global Change Biology, 2017)
Habitat degradation not only disrupts habitat‐forming species, but alters the sensory landscape within which most species must balance behavioural activities against predation risk. Rapidly developing a cautious behavioural phenotype, a condition known as neophobia, is advantageous when entering a novel risky habitat. Many aquatic organisms rely on damage‐released conspecific cues (i.e. alarm cues) as an indicator of impending danger and use them to assess general risk and develop neophobia. This study tested whether settlement‐stage damselfish associated with degraded coral reef habitats were able to use alarm cues as an indicator of risk and, in turn, develop a neophobic response at the end of their larval phase. Our results indicate that fish in live coral habitats that were exposed to alarm cues developed neophobia, and, in situ , were found to be more cautious, more closely associated with their coral shelters and survived four‐times better than non‐neophobic control fish. In contrast, fish that settled onto degraded coral habitats did not exhibit neophobia and consequently suffered much greater mortality on the reef, regardless of their history of exposure to alarm cues. Our results show that habitat degradation alters the efficacy of alarm cues with phenotypic and survival consequences for newly settled recruits.

Thermal environment and nutritional condition affect the efficacy of chemical alarm cues produced by prey fish - Govinda D. H. Lienart; Maud C. O. Ferrari; Mark I. McCormick (Environmental Biology of Fishes, 2016)

Geological connectivity drives microbial community structure and connectivity in polar, terrestrial ecosystems - Belinda C. Ferrari; Andrew Bissett; Ian Snape; Josie van Dorst; Anne S. Palmer; Mukan Ji; Steven D. Siciliano; Jonathon S. Stark; Tristrom Winsley; Mark V. Brown (Environmental Microbiology, 2016)
Summary Landscape heterogeneity impacts community assembly in animals and plants, but it is not clear if this ecological concept extends to microbes. To examine this question, we chose to investigate polar soil environments from the Antarctic and Arctic, where microbes often form the major component of biomass. We examined soil environments that ranged in connectivity from relatively well‐connected slopes to patchy, fragmented landforms that comprised isolated frost boils. We found landscape connectedness to have a significant correlation with microbial community structure and connectivity, as measured by co‐occurrence networks. Soils from within fragmented landforms appeared to exhibit less local environmental heterogeneity, harboured more similar communities, but fewer biological associations than connected landforms. This effect was observed at both poles, despite the geographical distances and ecological differences between them. We suggest that microbial communities inhabiting well‐connected landscape elements respond consistently to regional‐scale gradients in biotic and edaphic factors. Conversely, the repeated freeze thaw cycles that characterize fragmented landscapes create barriers within the landscape and act to homogenize the soil environment within individual frost boils and consequently the microbial communities. We propose that lower microbial connectivity in the fragmented landforms is a function of smaller patch size and continual disturbances following soil mixing.

Microbial diversity at Mitchell Peninsula, Eastern Antarctica: a potential biodiversity “hotspot” - Mukan Ji; Josie van Dorst; Andrew Bissett; Mark V. Brown; Anne S. Palmer; Ian Snape; Steven D. Siciliano; Belinda C. Ferrari (Polar Biology, 2016)

Specific global responses to N and Fe nutrition in toxic and non‐toxic Microcystis aeruginosa - Ralitza Alexova; The Cuong Dang; Manabu Fujii; Mark J. Raftery; T. David Waite; Belinda C. Ferrari; Brett A. Neilan (Environmental Microbiology, 2016)
Summary The bloom‐forming cyanobacteria species M icrocystis aeruginosa includes toxic and non‐toxic (microcystin‐producing) strains. Certain stress conditions stimulate synthesis of microcystin ( MCYST ) and enhance the binding of the MCYST molecule to proteins. In this quantitative proteomic study, we compared the response of a wild‐type toxic strain PCC 7806, an mcyH − knockout non‐toxic strain, and a naturally occurring non‐toxic strain, PCC 7005, after 8 days in low iron ( F e) and nitrogen ( N ) starvation in order to assess the benefit of MCYST synthesis in non‐optimal conditions. Fe limitation increased MCYST synthesis and caused an accumulation of phycobilisome proteins and the ferric iron transporter FutA only in the toxic PCC 7806 but not the non‐toxic strains. In N starvation, photosynthetic, C and N metabolism proteins were more abundant in the non‐toxic strains, as were chaperones and proteases. Significant interaction between nutrient availability and toxicity existed for thioredoxin peroxidase and several thioredoxin‐regulated proteins. We propose a competition of MCYST for binding sites in thioredoxin‐regulated proteins during oxidative stress (low F e) but not in growth‐limiting conditions (low N ). This then leads to differences in the regulation of C : N metabolism in toxic and non‐toxic M . aeruginosa in nutrient‐replete and nutrient‐limited conditions.

Interactive effects of ocean acidification and rising sea temperatures alter predation rate and predator selectivity in reef fish communities - Maud. C. O. Ferrari; Philip L. Munday; Jodie L. Rummer; Mark I. McCormick; Katherine Corkill; Sue‐Ann Watson; Bridie J. M. Allan; Mark G. Meekan; Douglas P. Chivers (Global Change Biology, 2015)
Ocean warming and acidification are serious threats to marine life. While each stressor alone has been studied in detail, their combined effects on the outcome of ecological interactions are poorly understood. We measured predation rates and predator selectivity of two closely related species of damselfish exposed to a predatory dottyback. We found temperature and CO 2 interacted synergistically on overall predation rate, but antagonistically on predator selectivity. Notably, elevated CO 2 or temperature alone reversed predator selectivity, but the interaction between the two stressors cancelled selectivity. Routine metabolic rates of the two prey showed strong species differences in tolerance to CO 2 and not temperature, but these differences did not correlate with recorded mortality. This highlights the difficulty of linking species‐level physiological tolerance to resulting ecological outcomes. This study is the first to document both synergistic and antagonistic effects of elevated CO 2 and temperature on a crucial ecological process like predator–prey dynamics.

Impaired learning of predators and lower prey survival under elevated CO 2 : a consequence of neurotransmitter interference - Douglas P. Chivers; Mark I. McCormick; Göran E. Nilsson; Philip L. Munday; Sue‐Ann Watson; Mark G. Meekan; Matthew D. Mitchell; Katherine C. Corkill; Maud C. O. Ferrari (Global Change Biology, 2014)
Ocean acidification is one of the most pressing environmental concerns of our time, and not surprisingly, we have seen a recent explosion of research into the physiological impacts and ecological consequences of changes in ocean chemistry. We are gaining considerable insights from this work, but further advances require greater integration across disciplines. Here, we showed that projected near‐future CO 2 levels impaired the ability of damselfish to learn the identity of predators. These effects stem from impaired neurotransmitter function; impaired learning under elevated CO 2 was reversed when fish were treated with gabazine, an antagonist of the GABA ‐A receptor – a major inhibitory neurotransmitter receptor in the brain of vertebrates. The effects of CO 2 on learning and the link to neurotransmitter interference were manifested as major differences in survival for fish released into the wild. Lower survival under elevated CO 2 , as a result of impaired learning, could have a major influence on population recruitment.

Connectivity of Caribbean coral populations: complementary insights from empirical and modelled gene flow - NICOLA L. FOSTER; CLAIRE B. PARIS; JOHNATHAN T. KOOL; ILIANA B. BAUMS; JAMIE R. STEVENS; JUAN A. SANCHEZ; CAROLINA BASTIDAS; CLAUDIA AGUDELO; PHILLIPPE BUSH; OWEN DAY; RENATA FERRARI; PATRICIA GONZALEZ; et al. (Molecular Ecology, 2012)
Understanding patterns of connectivity among populations of marine organisms is essential for the development of realistic, spatially explicit models of population dynamics. Two approaches, empirical genetic patterns and oceanographic dispersal modelling, have been used to estimate levels of evolutionary connectivity among marine populations but rarely have their potentially complementary insights been combined. Here, a spatially realistic Lagrangian model of larval dispersal and a theoretical genetic model are integrated with the most extensive study of gene flow in a Caribbean marine organism. The 871 genets collected from 26 sites spread over the wider Caribbean subsampled 45.8% of the 1900 potential unique genets in the model. At a coarse scale, significant consensus between modelled estimates of genetic structure and empirical genetic data for populations of the reef‐building coral Montastraea annularis is observed. However, modelled and empirical data differ in their estimates of connectivity among northern Mesoamerican reefs indicating that processes other than dispersal may dominate here. Further, the geographic location and porosity of the previously described east–west barrier to gene flow in the Caribbean is refined. A multi‐prong approach, integrating genetic data and spatially realistic models of larval dispersal and genetic projection, provides complementary insights into the processes underpinning population connectivity in marine invertebrates on evolutionary timescales.

Intrageneric variation in antipredator responses of coral reef fishes affected by ocean acidification: implications for climate change projections on marine communities - MAUD C. O. FERRARI; DANIELLE L. DIXSON; PHILIP L. MUNDAY; MARK I. McCORMICK; MARK G. MEEKAN; ANDREW SIH; DOUGLAS P. CHIVERS (Global Change Biology, 2011)
Our planet is experiencing an increase in the concentration of atmospheric carbon dioxide (CO 2 ) unprecedented in the past 800 000 years. About 30% of excess atmospheric CO 2 is absorbed by the oceans, thus increasing the concentration of carbonic acid and reducing the ocean's pH. Species able to survive the physiological stress imposed by ocean acidification may still suffer strong indirect negative consequences. Comparing the tolerance of different species to dissolved CO 2 is a necessary first step towards predicting the ecological impacts of rising CO 2 levels on marine communities. While it is intuitive that not all aquatic species will be affected the same way by CO 2 , one could predict that closely related species, sharing similar life histories and ecology, may show similar tolerance levels to CO 2 . Our ability to create functional groups of species according to their CO 2 tolerance may be crucial in our ability to predict community change in the future. Here, we tested the effects of CO 2 exposure on the antipredator responses of four damselfish species ( Pomacentrus chrysurus, Pomacentrus moluccensis, Pomacentrus amboinensis and Pomacentrus nagasakiensis ). Although being sympatric and sharing the same ecology and life history, the four congeneric species showed striking and unexpected variation in CO 2 tolerance, with CO 2 ‐induced loss of response to predation risk ranging from 30% to 95%. Using P. chrysurus as a model species, we further tested if these behavioural differences translated into differential ability to survive predators under natural conditions. Our results indicate that P. chrysurus larvae raised under CO 2 levels predicted by 2070 and 2100 showed decreased antipredator responses to risk, leading to a five‐ to sevenfold increase in predation‐related mortality in the first few hours of settlement. Examining ocean acidification, along with other environmental variables, will be a critical step in further evaluating ecological responses to predicted climatic change.

Long‐term survival of humpback whales radio‐tagged in Alaska from 1976 through 1978 - Sally A. Mizroch; Michael F. Tillman; Susan Jurasz; Janice M. Straley; Olga Von Ziegesar; Louis M. Herman; Adam A. Pack; Scott Baker; Jim Darling; Debbie Glockner‐Ferrari; Mark Ferrari; Dan R. Salden; et al. (Marine Mammal Science, 2011)
Invasive tags designed to provide information on animal movements through radio or satellite monitoring have tremendous potential for the study of whales and other cetaceans. However, to date there have been no published studies on the survival of tagged animals over periods of years or decades. Researchers from the National Marine Mammal Laboratory and the Woods Hole Oceanographic Institution tracked five humpback whales with implanted radio tags in southeastern Alaska in August 1976 and July 1977, and tracked two humpback whales in Prince William Sound, Alaska, in June 1978. All seven of these individually identified humpback whales were resighted at least 20 yr after first being tagged, and five of the seven have been observed for more than 30 yr; some of them are among the most resighted humpback whales in the North Pacific. Photos of tagging sites taken during and subsequent to tagging operations show persistent but superficial scarring and no indication of infection. These pioneering field studies demonstrated both long‐term survival of the whales and the short‐term effects of deploying radio tags, which at the time were larger and more invasive than those typically used today.

Molecular analysis of the efficiency of sloughed skin sampling in whale population genetics - ELENA VALSECCHI; DEBBIE GLOCKNER‐FERRARI; MARK FERRARI; WILLIAM AMOS (Molecular Ecology, 1998)
Sloughed whale skin contains enough DNA for genetic analysis, and offers a nonintrusive method for collecting tissue. Here, we examine the efficiency of sloughed skin sampling using 1460 samples collected from free‐ranging humpback whales. Samples were sexed and screened for up to 10 microsatellite markers. The vast majority of samples appear genetically compatible with field observations. About 1% of groups revealed more genotypes than whales, but we argue that this is more likely to be due to unobserved whales than to contamination. Sloughed skin sampling is particularly effective when applied to active groups and offers a viable alternative to biopsy darting in regions where darting is either not permitted or otherwise undesirable.

MALE HUMPBACK WHALE DIES IN COMPETITIVE GROUP - Adam A. Pack; Dan R. Salden; Mark J. Ferrari; Debbie A. Glockner‐Ferrari; Louis M. Herman; Harrison A. Stubbs; Janice M. Straley (Marine Mammal Science, 1998)